A Study on the Impact of Learning Environment on Higher Vocational College Students in Shandong Province, China: A Value-added Assessment Perspective (Journal of Interdisciplinary Insights, 2024)
This study examines the impact of the learning environment on student outcomes in higher vocational colleges in Shandong Province, China, from a value-added assessment perspective. Using Astin's Theory of Student Involvement as the theoretical framework, the research employs a quantitative methodology to analyze data collected from 300 students across three vocational colleges in Shandong, college A, B and C. The analysis highlights the significant influence of various components of the learning environment—social, academic, and administrative—on academic performance and skill development. Key findings suggest that positive peer relationships, faculty interactions, active student involvement in academic and extracurricular activities, and well-structured curricula with innovative teaching methods are crucial for student success. Administrative support and modern physical resources also play important roles. Based on these insights, the study proposes recommendations to enhance the learning environment, including the implementation of peer mentorship programs, expansion of extracurricular activities, continuous curriculum updates, and investment in modern facilities. These measures aim to create a holistic educational experience that fosters both academic excellence and practical skill development, preparing students for successful careers.